Co nowego w cholestazie - część 2. Cholestaza z podwyższoną aktywnością gamma-glutamylotranspeptydazy - Lipiński, Patryk; Jankowska, Irena (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Cholestatic liver diseases remain a major clinical issue for pediatricians. The article constitutes an up-to-day overview on cholestasis with elevated serum gamma-glutamyl transpeptidase activity. Authors presented the pathogenicity, clinical presentation, biochemical and molecular diagnostics of the following disorders: progressive familial intrahepatic cholestasis type 3, adenosine kinase deficiency, neonatal ichthyosis - sclerosing cholangitis syndrome.